Capsaicin Attenuates Arterial Calcification Through Promoting SIRT6-Mediated Deacetylation and Degradation of Hif1α (Hypoxic-Inducible Factor-1 Alpha). Issue 5 (2nd March 2022) - Luo, Dongling; Li, Wenxin; Xie, Changming; Yin, Li; Su, Xiaoyan; Chen, Jie; Huang, Hui
Abstract : Background: Sustained Hif1α (hypoxic-inducible factor-1 alpha) accumulation plays a central role in osteogenic transdifferentiation and subsequent calcification. Capsaicin, the potent agonist of TRPV1 (transient receptor potential vanilloid type 1), was found to mitigate hypoxic-related injury and reverse phenotypic switch of vascular smooth muscle cells. However, its role in arterial calcification and the underlying mechanisms remain unexplored. Methods: We used data from Multi-Ethnic Study of Atherosclerosis to examine the association of coronary artery calcification and chili consumption. Chronic kidney disease mice and high phosphate–induced vascular smooth muscle cells calcification models were established to investigate the anticalcification effect of capsaicin, evaluated by calcium deposition and changes in phenotype markers. Results: Chili consumption was negatively correlated with coronary artery calcification and conferred a smaller progression burden during follow-up. Capsaicin reduced calcium deposition and osteogenic transdifferentiation both in vivo and in vitro. Using siTRPV1 (small interfering RNA and the antagonist of TRPV1), the anticalcification effect of capsaicin was abrogated. Hif1α was increased in phosphate-treated vascular smooth muscle cells and its degradation was accelerated by capsaicin. Retaining Hif1α stability using cobalt chloride (CoCl2 ) or MG132 abolished the protective effect of capsaicin. We further identified an increased expression of SIRT6 (Sirtuin 6) in response to capsaicin and confirmed the physical interaction between SIRT6 and Hif1α. Acetylated Hif1α was decreased, whereas hydroxylated Hif1α was increased under capsaicin treatment. Using immunohistochemistry analysis, we observed increased SIRT6 and reduced Hif1α in both SIRT6 transgenic and capsaicin-treated chronic kidney disease mice. Conclusions: Capsaicin facilitates deacetylation and degradation of Hif1α by upregulating SIRT6, which inhibits osteogenic transdifferentiation and protects against arterial calcification. These data highlight a promising therapeutic target for the management of arterial calcification.